Morphologic variants of Meibomian glands: age-wise distribution and differences between upper and lower eyelids - Srivastav, Saumya; Hasnat Ali, Mohammed; Basu, Sayan; Singh, Swati (Frontiers in Medicine, 2023)
Purpose To evaluate the distribution of various Meibomian gland morphologies across different age groups in healthy individuals. Methods The infrared meibographic morphologies of the Meibomian glands from the upper and lower eyelids of 236 healthy individuals (472 eyes; mean age 38.4 ± 17.5 years; 80 female participants: 156 male participants) were evaluated for their prevalence and differences across six decades of life, from 10 to 80 years. A linear mixed-effects modeling test was performed for statistical analysis. Results Of 14,452 glands, 8,830 (61%) glands were located in the upper eyelid. No significant differences in frequency were noted between different age groups for distorted, tortuous, hooked, overlapping, abnormal gap, fluffy areas, dropout (except for 51–60 vs. 10–20 years, P = 0.023), and thick and thin morphologies. Short glands were significantly more common in individuals aged over 30 years (P = 0.015), whereas moderately short and severely short glands were more common in the upper eyelids of individuals older than 50 years compared to those aged 10–20 years (P = 0.035). The frequency of distorted, hooked, tortuous, overlapping, and tadpole-shaped Meibomian glands was significantly higher in the upper eyelids than in the lower eyelids for all age groups. Dropout glands were more common in the lower eyelids of individuals younger than 50 years, but no difference was observed in the upper and lower eyelids of individuals over 50 years. Dropout (P = 0.006) and severely short glands (0.026) of the lower eyelid were associated with low non-invasive tear break-up time (NIBUT) values. Conclusion Various morphologic characteristics of the Meibomian glands that are considered abnormal can be present in healthy individuals, and only moderate to severely short glands display an increase in abnormal morphologic characteristics of the Meibomian glands with age.